Risk factor analysis of diarrhoeal disease incidence in faecal sludge-applying farmers' households in Tamale, Ghana - Seidu, R.; Lofman, O.; Drechsel, Pay; Stenstrom, T.A. (IWA Publishing, 2013)
This study assesses the effect of risk factors and their inter-related mediation on diarrhoeal disease incidence in households applying faecal sludge in agricultural fields in Tamale, Ghana. Risk factors were assigned to three inter-related blocks: distal socio-economic, proximal public and domestic domains. The study involved 1,431 individuals living in 165 faecal sludge-applying households followed bi-weekly for 12 months. The incidence rate of diarrhoeal disease in the sludge-applying households was 1.09 (95% CI: 0.78-1.23) diarrhoeal episodes per person year at risk. Risk factors for diarrhoeal disease transmission in the public domain included sludge drying time (population attributable fraction (PAF) of 6%) and distance covered to collect water (PAF? 18%). The main distal socio-economic risk factor was wealth status (PAF? 15%). In the domestic domain, the risk factor significantly associated with diarrhoeal disease transmission was, not washing hands with soap after defecation (PAF ? 18%). About 17% of the effect of sludge drying time (including distance to water facilities) was mediated by the domestic domain risk factors. The study recommends risk management strategies in sludge-applying households that address public and domestic domain risk factors in addition to specific farm level interventions.